THE LOVE BETWEEN MR. DARCY AND MS. ELIZABETH IN THE WORK “PRIDE AND PREJUDICE” BY JANE AUSTEN = TÌNH YÊU GIỮA MR. DARCY AND MS. ELIZABETH TRONG TÁC PHẨM ‘‘KIÊU HÃNH VÀ ĐỊNH KIẾN’’ CỦA JANE AUSTEN - Nguyễn, Thị Thu Hằng (2021)
I watched the movie “Pride and Prejudice” a few of years ago and I have had a deep impression on the movie. Therefore, when doing the thesis, I choose it to be able to understand the novel more. The main topic of the work “Pride and Prejudice”, written by the female author Jane Austen, is love and marriage in the eighteenth century. Among a large number of love stories in the work, the love between Mr. Darcy and Ms. Elizabeth is the most cherished love affair in my mind and I want to discover the author’s implication as well as her own opinions through the couple. In order to fulfill my research, I use certain research methods such as searching the Internet, reading review books, discussing with people who like this work, including my supervisor, and exchanging opinions on literature forum. In general, I hope that in these way, I can listen to more ideas, acknowledge more reviews and have a more critical and multidirectional view on the topic. In the work, there are a number of marriages symbolizing some types of marriages in the eighteenth century society. However, just the love between Mr. Darcy and Ms. Elizabeth can impress the readers and me. It is because their love goes beyond the context of the eighteenth century and is ideal love human beings want to have. In my mind, their love is not only passionate but also intense. The more ardent their love is, the more powerful it is. The intense love helps them overcome both internal barriers- their pride and prejudice and external barriers formed by their relatives and friends. Specifically, their powerful love overcomes the prejudices of the eighteenth century. In addition, the ardency in their love impresses me very much because it has hidden inside them for a long time and not expressed outside until the end of the work. In my thesis, I exploit the details in the work to make clear how intense and passionate their love is.